Efektivitas Music Relaxation Therapy (MRT) terhadap Penurunan Tingkat Stres pada Pasien Hipertensi: Studi Kuasi-Eksperimen di Desa Asembagus - Heru, Maulidiyah Junnatul Azizah; Qomariyah, Alvin Nanda Nuril; Yuniar, Aulia Putri; Putri, Arifka Alifia Dwi; Bariroh, Afifatul; Hasanah, Aprilianti Dwi Nur; Rosyadah, Amirina (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Hypertension is a non-communicable disease whose prevalence is increasing and is a leading cause of morbidity and mortality. Unmanaged psychological stress contributes to increased blood pressure and exacerbates the condition of hypertension. This study aims to evaluate the effectiveness of Music Relaxation Therapy (MRT) in reducing stress in hypertensive patients. The research design used was a quasi-experiment with a one-group pre-test and post-test approach, involving 30 hypertensive patients aged 30-60 years from Asembagus Village, Kraksaan, Probolinggo, who experienced stress based on the DASS-42 instrument, which has been translated and validated. The intervention consisted of playing relaxation music (instrumental music with a slow tempo and calming frequencies) for 20 minutes every morning for fifteen consecutive days. Stress levels were measured before and after the intervention. Statistical testing used the non-parametric Wilcoxon signed rank test because of paired data that did not follow a normal distribution. The analysis results showed a significant reduction in stress levels (Z = -4.718 and p = 0.000). These findings indicate that MRT is statistically effective in reducing stress in hypertensive patients. The practical contribution of this study is that MRT can be a non-pharmacological approach that is easy to implement and affordable, offering an alternative therapy to reduce stress in hypertensive patients.